Utilization of the ARIMA Model for Predicting the Value of Coconut Export in Kalimantan Barat - Marda, Marda; Imro'ah, Nurfitri; Novita, Irene (Jurnal Forum Analisis Statistik, 2024)
The manufactured coconut classified under HS code 08011100 is available in either shredded or dried form. In 2022, this variety of coconut is projected to account for 8.68% of the export value of manufactured coconuts in Indonesia. While West Kalimantan has not yet achieved the status of the largest coconut exporter in Indonesia, coconut remains the primary commodity in the plantation sub-sector and significantly contributes to the Regional Original Income (PAD) of West Kalimantan Province. West Kalimantan, with a potential coconut plantation area of 94,204 ha and a growing array of processed coconut products, stands poised to enhance the value of its coconut exports. This study seeks to examine prospective market conditions by predicting the export value of coconuts in shredded or dried form, serving as a foundational strategy for enhancing the value of coconut exports. The ARIMA (Autoregressive Integrated Moving Average) model is employed to forecast the value of coconut exports (HS 08011100) for the upcoming 4 periods. During the process of identifying the best model, the ARIMA model (2,1,1) was selected, yielding a MAPE value of 26.63%. This indicates that the forecasts for coconut export values (HS 08011100) remain acceptable. The estimated coconut export value serves as a valuable planning reference for stakeholders aiming to enhance future coconut exports.